FAT3 Mutation Is Associated With Tumor Mutation Burden and Poor Prognosis in Esophageal Cancer - Guo, Zixin; Yan, Xin; Song, Congkuan; Wang, Qingwen; Wang, Yujin; Liu, Xiao-Ping; Huang, Jingyu; Li, Sheng; Hu, Weidong (Frontiers in Oncology, 2021)
Objective To explore the mutated genes in esophageal cancer (ESCA), and evaluate its relationship with tumor mutation burden (TMB) and prognosis of ESCA, and analyze the advantages of FAT3 as a potential prognostic marker in ESCA. Methods The somatic mutation landscape was analyzed according to ESCA samples from the TCGA and ICGC database. The differences of TMB between mutant type and wild type of frequently mutated genes were compared by Mann-Whitney U test. The association of gene mutations with prognosis was analyzed by Kaplan-Meier method. The relative abundance of 22 tumor-infiltrating lymphocyte subsets in ESCA was calculated by CIBERSORT algorithm. Results FAT3 was a high frequency mutation in both TCGA and ICGC samples from the somatic mutation landscape. Then, the mutation type of FAT3 had significantly higher TMB in patients with ESCA compared the wild type (P<0.05). Meanwhile, the prognosis of FAT3 mutation type was significantly worse in patients with ESCA(P<0.05), and the FAT3 mutation status might be an independent factor for prognosis of patients with ESCA (HR: 1.262–5.922, P=0.011). The GSEA analysis revealed the potential mechanism of FAT3 mutation on the occurrence and development of ESCA. Finally, naive B cells were significantly enriched in FAT3 mutation samples of the ESCA microenvironment (P<0.05). Conclusions FAT3 mutation is related to TMB and poor prognosis in ESCA. FAT3 mutation may be a prognostic marker of ESCA, and reveal the potential mechanism of FAT3 mutation on ESCA.